PENGARUH PENILAIAN CITRA MEREK DAN INTENSITAS TERPAAN TESTIMONI NEGATIF TENTANG PELAYANAN JNE DI MEDIA ONLINE TERHADAP TINGKAT KEPERCAYAAN MASYARAKAT UNTUK MENGGUNAKAN JNE - Putrika Nayana Pradhanika; Adi Nugroho; Muhammad Bayu Widagdo (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2023)
JNE is known as one of the biggest Indonesian logistics and freight forwarding companies. Even though JNE has won the Top Brand Index title for the Courier Service Category 8 times, it turns out that JNE often gets negative testimonials or complaints from its customers. This research aims to see the influence of brand image and exposure of bad testimonials about JNE's service in digital media to the level of public trust to use JNE. The theories used in this research are Expectancy-value Theory and Information Integration Theory by Philip Palmgreen. In determining the sample, this research used a non-probability sampling technique with a sample of 50 people, male or female, aged 18-35 years, often doing online shopping, had to use JNE’s service, and also had read bad testimonials about JNE’s service in digital media. The test is carried out using the Ordinal Regression Test. The results showed that brand image perception influences the level of public trust to use JNE. Furthermore, there is a significance correlation between the intensity exposure of bad testimonials about JNE's service in digital media with the level of public trust to use JNE